Tele-ICU in the Unites States: Is a cost-effective model?. (2nd October 2022) - Michael Robie, E.; Cole, Stephanie; Suwal, Archana; Coustasse, Alberto
ABSTRACT: Introduction: The United States Society of Critical Care Medicine has announced a shortage of all critical care intensivists due to the increased need for critical care for the aging population with comorbidities and improved life expectancy. This shortage has led to tele-ICU programs that have allowed intensivists to care for patients simultaneously remotely. Methods: This study aimed to assess the potential for the hospital implementation of tele-ICU to determine its overall healthcare cost-effectiveness. The methodology was a review that followed a systematic search approach utilizing 42 sources. Results: The study findings showed that tele-ICU contributed to reduced hospital LOS by 36% and positive financial outcomes of return of investment and cost-effectiveness. These reduced LOS stay times have allowed for savings up to $11.5 million. Discussion: The Tele-ICU program's implementation has positively impacted financial and clinical areas, reducing mortality and reduced hospital LOS. Furthermore, it has reduced improved patient safety, care quality, and decreased ventilator days, contributing to a cost-efficient technology.